An unprecedented up-field shift in the 13C NMR spectrum of the carboxyl carbons of the lantern-type dinuclear complex TBA[Ru2(O2CCH3)4Cl2] (TBA+ = tetra(n-butyl)ammonium cation) - Hiraoka, Yuya; Ikeue, Takahisa; Sakiyama, Hiroshi; Guégan, Frédéric; Luneau, Dominique; Gillon, Béatrice; Hiromitsu, Ichiro; Yoshioka, Daisuke; Mikuriya, Masahiro; Kataoka, Yusuke; Handa, Makoto (Dalton transactions : an international journal of inorganic chemistry, 2015)
A large up-field shift (-763 ppm) has been observed for the carboxyl carbons of the dichlorido complex TBA[Ru(2)(O(2)CCH(3))(4)Cl(2)] (TBA(+) = tetra(n-butyl)ammonium cation) in the (13)C NMR spectrum (CD(2)Cl(2) at 25 °C). The DFT calculations showed spin delocalization from the paramagnetic Ru(2)(5+) core to the ligands, in agreement with the large up-field shift.